2004
DOI: 10.1080/10720530490250679
|View full text |Cite
|
Sign up to set email alerts
|

Content Analysis of the Personal Constructs of Female Sexual Abuse Survivors Elicited Through Repertory Grid Technique

Abstract: Construct contents of college women with a history of childhood sexual abuse were compared to those of college women with no abuse history using Landfield's (1971) content coding system. The sexual abuse survivors were best discriminated by fewer constructs referring to emotional arousal; to experiences of calm, peacefulness, and relaxation (low forcefulness), and to moral or religious standards. Abused women also used more factual descriptions and fewer constructs referring to freedom from care (low involveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
(30 reference statements)
0
10
0
4
Order By: Relevance
“…One form of trauma that has received specific research attention is childhood sexual abuse, the long-term effects of which have been shown to include construing of the self as dissimilar to one's parents and other people, and particular features of the content of the construct system, such as limited use of emotional constructs (Bhandari, Winter, Messer, & Metcalfe, 2011;Freshwater, Leach, & Aldridge, 2001;Harter, 2000;Harter, Alexander, & Neimeyer, 1988;Harter, Erbes, & Hart, 2004;Harter & Neimeyer, 1995). While posttraumatic stress reactions have more commonly been studied in the victims of abuse than in its perpetrators, a significant proportion of people who commit acts of violence have been reported to display such reactions (Collins & Bailey, 1990;Dutton, 1995;Kruppa, Hickey, & Hubbard, 1995;Steiner, Garcia, & Matthews, 1997).…”
mentioning
confidence: 96%
“…One form of trauma that has received specific research attention is childhood sexual abuse, the long-term effects of which have been shown to include construing of the self as dissimilar to one's parents and other people, and particular features of the content of the construct system, such as limited use of emotional constructs (Bhandari, Winter, Messer, & Metcalfe, 2011;Freshwater, Leach, & Aldridge, 2001;Harter, 2000;Harter, Alexander, & Neimeyer, 1988;Harter, Erbes, & Hart, 2004;Harter & Neimeyer, 1995). While posttraumatic stress reactions have more commonly been studied in the victims of abuse than in its perpetrators, a significant proportion of people who commit acts of violence have been reported to display such reactions (Collins & Bailey, 1990;Dutton, 1995;Kruppa, Hickey, & Hubbard, 1995;Steiner, Garcia, & Matthews, 1997).…”
mentioning
confidence: 96%
“…The constructs are personal and group constructs are only constructed later in the process. Fransella et al (2004) cite various examples of both idiographic and nomothetic use of RepGrid. These are reported as being in line with Kelly's own views that the one approach should not be to the exclusion of the other.…”
Section: Reasons For Using the Repgrid Techniquementioning
confidence: 99%
“…Some constructs were assigned to more than one code, or the poles of the construct were assigned to different codes (Ellis-Scheer, 2000;Harter et al, 2004). This occurred particularly with nested codes (Feixas et al, 2002, p. 9).…”
Section: Analysis Of the Constructsmentioning
confidence: 99%
“…Importantly, this decision also ensured that the analysis remained as close as possible to the participants' own words (Harter et al, 2004;Jankowicz, 2004;Leach, Freshwater, Aldridge, & Sunderland, 2001). …”
Section: Analysis Of the Constructsmentioning
confidence: 99%
See 1 more Smart Citation